Bearing capacity beneath tapered blades of open dug caissons in sand - Royston, R; Phillips, B; Sheil, B; Byrne, B (Civil Engineering Research Association of Ireland, 2016)
An open-dug caisson shaft is a form of top-down construction in which a concrete shaft is sunk into the ground using the weight of the shaft and additional kentledge, if required. Excavation at the base of the caisson shaft wall allows the structure to descend through the ground. A thorough understanding of the interaction between the caisson shaft and soil is essential to maintain controlled sinking of the caisson. In this paper, the failure mechanisms developed beneath caisson blades in sand are investigated. A series of laboratory tests were carried out at the University of Oxford to explore how varying blade angles affect the performance of the bearing capacity beneath the caisson. Cutting angles of 30°, 45°, 60°, 75° and 90° (flat) were penetrated into sand under plane strain conditions; forces were monitored using a Cambridge-type load cell while soil displacements were recorded using Particle Image Velocimetry (PIV) techniques. The aim of this study is to understand how the soil failure mechanism develops and to determine the optimum cutting angle. The results of the laboratory tests can be scaled to predict the likely behaviour in the field. Results show that the bearing capacity is significantly dependent on the cutting angle; in a dense sand a steep cutting angle may be used to aid sinking of the caisson.